Systematic Literature Review of Entrepreneurial Orientation, Financial Literacy, Good Governance, and Digital Leadership in the Context of Organizational Performance - Suherman, Acep; Agoes, Sukrisno; Ahmar, Nurmala (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study aims to conduct a Systematic Literature Review (SLR) to analyze the development of research related to entrepreneurial orientation, financial literacy, good governance, and digital leadership in the context of organizational performance during the period 2019–2024. The research method used is descriptive qualitative, involving the collection and analysis of 45 selected journals from databases such as Google Scholar, Scopus, and accredited journal websites. Key findings reveal that the four variables (entrepreneurial orientation, financial literacy, good governance, digital leadership) interact and significantly influence organizational performance, both directly and indirectly through mediation and moderation mechanisms. Furthermore, this study identifies that these themes remain relevant and widely researched, particularly in the contexts of education, MSMEs, and the public sector. Practical implications of this research emphasize the importance of implementing good governance principles, enhancing financial literacy, strengthening entrepreneurial orientation, and developing digital leadership to achieve superior and sustainable organizational performance This study successfully synthesizes and confirms the existence of dynamic and mutually reinforcing interactions among entrepreneurial orientation, financial literacy, good governance, and digital leadership in driving organizational performance. Furthermore, this article serves as a research roadmap for academics and practitioners seeking to understand the latest dynamics in the fields of digital leadership, governance, entrepreneurship, and financial literacy.